2016
DOI: 10.1007/s11307-016-0950-0
|View full text |Cite
|
Sign up to set email alerts
|

[18F]FDG PET Neuroimaging Predicts Pentylenetetrazole (PTZ) Kindling Outcome in Rats

Abstract: Non-invasive PET neuroimaging was a useful tool for discerning epileptogenesis progression in this animal model. Particularly, the [(18)F]FDG uptake of the hippocampus proved to be an early predictive parameter to differentiate resistant and non-resistant animals to the PTZ kindling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 43 publications
0
15
0
9
Order By: Relevance
“…Once the images were spatially normalized, we obtained the Standardized Uptake Value (SUV) for the regions of interest (ROI): nucleus accumbens, striatum, amygdala, prefrontal cortex, ventral tegmental area, hippocampus, hypothalamus, and cerebellum. The SUV value of each ROI was normalized to the SUV value of pons, obtaining SUV ratios (SUVr); this region is often used to normalize SUV values in brain (Kornblum et al, ; Guo et al, ; Bascuñana, et al, ). To increase the statistical power, all images were smoothed with an isotropic Gaussian kernel (0.6 mm full width at half‐maximum).…”
Section: Methodsmentioning
confidence: 99%
“…Once the images were spatially normalized, we obtained the Standardized Uptake Value (SUV) for the regions of interest (ROI): nucleus accumbens, striatum, amygdala, prefrontal cortex, ventral tegmental area, hippocampus, hypothalamus, and cerebellum. The SUV value of each ROI was normalized to the SUV value of pons, obtaining SUV ratios (SUVr); this region is often used to normalize SUV values in brain (Kornblum et al, ; Guo et al, ; Bascuñana, et al, ). To increase the statistical power, all images were smoothed with an isotropic Gaussian kernel (0.6 mm full width at half‐maximum).…”
Section: Methodsmentioning
confidence: 99%
“…C)—a “quiescent” time gap (about 2‐3 weeks) between the initial status epilepticus and the appearance of recurrent seizures (Goffin et al, ; Guo et al, ; Lee et al, ; Zhang et al, ). FDG‐PET imaging in another popular epilepsy model (PTZ‐kindling) also showed that animals with successful kindling (i.e., epileptic) all showed significant reductions of glucose utilization in multiple brain regions, while animals with “unsuccessful” kindling (i.e., those avoiding the epileptic state) all exhibited normal glucose metabolism (Bascunana et al, ). Importantly, this hypometabolism was not correlated with the MRI‐detected atrophy or pyramidal cell loss (Bascunana et al, ; Jupp et al, ), confirming that the initial stage of epileptogenesis is directly associated with the glucose metabolism dysfunction.…”
Section: Short Outline Of Main Glucose Functionsmentioning
confidence: 97%
“…B; Pan et al, ; Pittau et al, ). Interestingly, a similar technique used in a number of different animal models revealed that hypometabolism, indicated by reduced glucose consumption, is a very early sign of epileptogenesis (Bascunana et al, ; Goffin et al, ; Guo et al, ; Jupp et al, ; Lee et al, ; Zhang et al, ). In very severe epilepsy models like pilocarpine‐ or kainаte‐induced, where epileptogenesis is initiated via status epilepticus, significant glucose utilization deficiency has been detected in the latent period (Fig.…”
Section: Short Outline Of Main Glucose Functionsmentioning
confidence: 99%
“…Comparing [ 18 F] VAT PET with [ 18 F] FDG PET, we found that the former may have a particular advantage in exhibiting cholinergic dysfunction in basal forebrain in a chronic pilocarpine model. In addition, [ 18 F] FDG PET displays widespread hypometabolism at both subcortical and cortical levels, which could possibly be explained by overall reduction of neuronal activity in chronic epilepsy . In contrast, [ 18 F] VAT PET identifies cholinergic dysfunction at the subcortical level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we analyzed the caudate and putamen region, which is rich in cholinergic interneurons . The standardized uptake value of each ROI was calculated and normalized to pons …”
Section: Methodsmentioning
confidence: 99%